THE ROLE OF PARENTS IN CHILDREN'S GROWTH AT RAUDLATUL ISLAMIC PRE-SCHOOL - Kholifah, Siti; Yulianti, Sari; Rosita, Rosita; Nurhaelah, Nurhaelah; Rasitah, Hj; Rahmawati, Rahmawati; Muhayah, Siti; Yuliyanti, Siti Nur; Julaeha, Eha; Fadilah, Siti Fadilah; Khotimah, Siti; Anipah, Aan (International Journal of Engagement and Empowerment (IJE2), 2025)
Parents significantly influence the growth and development of early childhood, particularly during the "golden age." Parenting styles significantly shape children's physical, cognitive, social, and emotional development. This study analyzes the role of parents in the education, care, protection, and health of children using action research and literature study methods. The survey results indicate that good parenting patterns, balanced nutrition, and positive interactions support optimal child development. However, limited knowledge and resources are challenges. Therefore, parents must receive education on PKM (Community Service) activities or socialization of smart parenting, both offered at Paud Raudotul Islamiah, to provide care conducive to their children's optimal development.